Abundance and reproduction of porphyriops melanops in a suburban artificial wetland in Bogotá, Colombia (2016)
The Spot-flanked Gallinule Porphyriops melanops bogotensis is a subspecies endemic to the Cundinamarca-Boyacá highland plateau. It is critically endangered due to wetlands deterioration and it has been suggested that artificial wetlands may help in its conservation. Therefore, we examined the abundance and reproduction of this gallinule in an artificial wetland in the north of Bogotá, Colombia. We did monthly counts of chicks, sub adults and adults from May 2008 to May 2010 and recorded the duration of each developmental stage. Based on the observation of chicks we determined that gallinules reproduced multiple times in 2008 and 2009, but not in 2010. We found a negative correlation between the numbers of adults and the numbers of chicks and sub adults, suggesting a density-dependent effect. We found no correlation between abundance and rainfall. Monthly abundance of the gallinule during the study period in the natural wetland of Guaymaral, ~1 km from the study site, was negatively correlated with the abundance of gallinules in our artificial wetland. Approximately 46% of chicks became adults. The probability of chicks and sub adults of disappearing from the population was similar: ~0,3. Our results suggest that artificial wetlands can be source habitats for gallinules, and key aspects for the future use of artificial wetlands are: providing nesting sites, protecting them from domestic animals and humans, and maintaining connectivity with neighboring natural wetlands.